2020
DOI: 10.2337/dc20-2003
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Depressive Symptoms in Patients With Type 1 and Type 2 Diabetes in Developing Countries: Results From the International Diabetes Management Practices Study

Abstract: Depression is common in people with diabetes, but data from developing countries are scarce. We evaluated the prevalence and risk factors for depressive symptoms in patients with diabetes using data from the International Diabetes Management Practices Study (IDMPS). RESEARCH DESIGN AND METHODSIDMPS is an ongoing multinational, cross-sectional study investigating quality of care in patients with diabetes in real-world settings. Data from wave 5 (2011), including 21 countries, were analyzed using the 9-item Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
6
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
3
11
6
5
Order By: Relevance
“…The prevalence of depression found in this study through the SCID-I is low in comparison with the estimates of some authors, who place the prevalence of depression in patients with T1D at around 30% [ 12 , 14 , 21 ]. Perhaps, for this reason, the positive predictive value (PPV) is not very high in any of the three scales, although it is high enough to assure that the DID-1 confirms the disease.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The prevalence of depression found in this study through the SCID-I is low in comparison with the estimates of some authors, who place the prevalence of depression in patients with T1D at around 30% [ 12 , 14 , 21 ]. Perhaps, for this reason, the positive predictive value (PPV) is not very high in any of the three scales, although it is high enough to assure that the DID-1 confirms the disease.…”
Section: Discussioncontrasting
confidence: 97%
“…When assessing differences in DID-1 scores as a function of sample characteristics, we found that women scored worse than men on both the total scale score and the seven factors. These results are consistent with previous results and those found in the general population and in the population with diabetes, with a higher prevalence of depression in women [ 14 , 35 ]. With regard to complications, significant differences were found between those with physical illness and those without.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Conversely, this study's prevalence of depressive symptoms was relatively lower than previous studies conducted with diabetic adults in other countries. An international crosssectional study conducted with the PHQ-9 in 21 developing countries reported moderate to severe depressive symptoms in 10.2% and 11.1% in adults with type 1 and type 2 diabetes, respectively [8]. In Indonesia, a cross-sectional survey using the PHQ-9 identified that 11.6% of adults with diabetes exhibited depressive symptoms (PHQ-9 score ≥ 10) [36].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 39 studies showed that the likelihood of depression in people with diabetes was twice that of people without diabetes [7]. Approximately 10-20% of people with diabetes experience depressive symptoms and are more likely to have a moderate to severe form of depression [8][9][10][11]. The high burden of diabetes complications and diabetes itself can increase the risk of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%